"After all – It doesn't kill you to quit smoking": An explorative analysis of the blog in a smoking cessation intervention. Issue 7 (November 2013) - Brandt, Caroline Lyng; Dalum, Peter; Skov-Ettrup, Lise; Tolstrup, Janne Schurmann
Background : A growing body of literature demonstrates internet-based smoking cessation interventions as a promising aid in helping people quit smoking. However, the underlying mechanisms of how these interventions influence the cessation process are still relatively unknown. Several studies have indicated blogging as a potential source in providing social support to users of internet-based smoking cessation interventions and thereby enhance their change of succeeding in quitting. Objective : The study aimed to investigate themes discussed on a blog in an internet-based smoking cessation intervention. In addition, we examined if blogging could provide social support for people in a smoking cessation process. Method : The study was based on messages posted from 1 January 2012 to 29 February 2012 on the blog of the internet-based smoking cessation programme DDSP, operated by the Danish Cancer Society. Messages were coded according to themes using Grounded Theory, and additionally data about bloggers were analyzed. Result : In total, 1663 messages were posted within the 2-month period, and we identified 16 themes. The majority of messages contained personal stories or experiences (53%), provided emotional support (34%) or congratulated other users (17%). The messages were found capable of supplying social support to members on the blog. In addition, we found that only a minority of users who viewed the blog participated actively in posting messages, and only a minority was highly active bloggers. Conclusions : The blog offers a unique platform for informal conversations about quitting smoking and is important in providing social support to people in a smoking cessation process.